Intersectionality in feminist and queer movements: Confronting privileges - Evans, Elizabeth; Lépinard, Éléonore (Routledge, 2020)
Examining the ways in which feminist and queer activists confront privilege through the use of intersectionality, this edited collection presents empirical case studies from around the world to consider how intersectionality has been taken up (or indeed contested) by activists in order to expose and resist privilege. The volume sets out three key ways in which intersectionality operates within feminist and queer movements: it is used as a collective identity, as a strategy for forming coalitions, and as a repertoire for inclusivity. The case studies presented in this book then evaluate the extent to which some, or all, of these types of intersectional activism are used to confront manifestations of privilege. Drawing upon a wide range of cases from across time and space, this volume explores the difficulties with which activists often grapple when it comes to translating the desire for intersectionality into a praxis which confronts privilege. Addressing inter-related and politically relevant questions concerning how we apply and theorise intersectionality in our studies of feminist and queer movements, this timely edited collection will be of interest to students and scholars from across the social sciences and humanities with an interest in gender and feminism, LGBT+ and queer studies, and social movement studies.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; privilèges; queer; ressource en ligne; systèmes d'oppressions; thématiques

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Différence des sexes (Théorie de la) - Collin, Françoise (Dictionnaire critique du féminisme, 2000)
Dictionnaire théorique et politique, pluriel et engagé, il pose comme centrale la problématique de la domination entre les sexes et ses conséquences. Critique à double titre, il expose les controverses théoriques et politiques qui traversent la pensée et le mouvement féministe, et se propose de déconstruire certains concepts classiques des sciences sociales.
Keywords: 1900-1999; approches et analyses; cours; différence des sexes; europe; fem1000; france; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques